Fatal Intracranial Hemorrhage in a Pregnant Patient With Acute Promyelocytic Leukemia. (21st September 2018) - Zhang, Lin; Tomsula, Jessica; Lin, Mei; Wahed, Amer; Nguyen, Nghia; Tatevian, Nina; Chen, Lei
Abstract: Although the prognosis of acute promyelocytic leukemia (APL) is favorable because of disease-specific drugs, such as all- trans retinoic acid (ATRA), early death due to fatal intracranial hemorrhage (ICH) has been observed in some cases. Here we present a catastrophic ICH in a young pregnant woman with APL. Patient was a 23-year-old woman at 25 weeks' gestation with a 1-week history of lower extremity purpura; subsequently, she developed severe headache and altered mental status. She presented to the local ER and imaging revealed extensive ICH with tonsillar herniation. Peripheral blood smear showed significant leukocytosis with 97% of blasts. The blasts had a characteristic bilobed or reniform nucleus, with the majority of the cells either devoid of granules or contained only a few fine azurophilic granules. This is morphologically consistent with APL, hypogranular variant. Patient was in severe disseminated intravascular coagulation and ATRA was immediately administered. STAT flow on peripheral blood showed 93% blasts that were positive for CD13, CD33, CD117 (majority), and myeloperoxidase (MPO). AML/FISH results revealed PML-RARA fusion in 95.6% of cells tested. Due to fetal distress, an emergent cesarean section was performed. The placenta also showed multiple aggregates of large atypical cells within the maternal intervillous spaces. These cells were confirmed by immunostains as leukemic cells coming from the maternal circulation. Infant's peripheral blood upon delivery revealed very few myeloblasts, which is commonly seen in premature babies and newborns. Unfortunately, shortly following the diagnosis, both the mother and premature infant died. The occurrence of APL during pregnancy is a rare event, but the management is very critical as APL is associated with life-threatening consequences of DIC, which is present at diagnosis in most patients.